Photoautotrophic microorganisms with biotechnological potential unexplored - Rendón, Lina (2022)
The study of phototrophic organisms is becoming more common due to their high nutritional value and capacity to produce various bioactive compounds with potential use in food, pharmaceutical, nutraceutical, cosmeceutical, and chemical industries. These compounds have nutritional and therapeutic properties such as neuroprotective, antioxidant, anti-inflammatory, anticoagulant, hyperlipidemic, immunomodulatory, and immunoregulatory. For this reason, phototrophic organisms are an essential supply for different industries since they can satisfy their current commercial demand while reducing the environmental impact and promoting the bioeconomic development of the country. However, research on these microorganisms is still limited and focused on a limited group of species. This review examines the biotechnological applications of bioactive metabolites produced by several photoautotrophic microbial species from poorly explored environments and their industrial application. As a result, we could determine that there are many little-explored species with a wide variety of bioactive compounds. Moreover, they have potential uses in various industries such as nutraceuticals, cosmeceuticals, and energy. Furthermore, it was concluded that the bioindustry represents a business opportunity and can also be established as a platform for modernization and competitiveness for various country's economic sectors.